Pengaruh Sukuk, Reksadana Syariah dan Total Aset LKNB Syariah terhadap pertumbuhan ekonomi di Indonesia Tahun 2015-2021 - Azizah Mudrikah; Imsar Imsar (Owner : Riset dan Jurnal Akuntansi, 2023)
The principal The aim of the current study is to measure the effects of sukuk, sharia mutual funds, and total lknb sharia assets on Indonesian economic growth. Three independent variables (sukuk, sharia mutual funds, and total assets of sharia financial institutions) are combined with one dependent variable in this study (economic growth). This study's population is based on information from the Financial Services Authority  and the Central Statistics Agency  on sukuk, sharia mutual funds and total assets of sharia financial institutions for the last seven years, namely data from 2015-2020 period. 84 data points were interpolated and a saturated sample technique was used, that is all data from 2015 to 2021. The method of analysis process used is quantitative analysis with collected sources. According to the findings of this study, partial sukuk and total assets of sharia financial institutions have a significant and positive impact on economic growth. Meantime, Sharia mutual funds have a significant negative impact on economic growth. t table has a value of 1.990. count > t table of 5,178 > 1,990 which shows that sukuk influences economic growth in Indonesia. t count > t table of 17,562 > 1,990 which shows that Islamic mutual funds influence economic growth in Indonesia. and t count > t table of 9.0819 > 2.0032 which shows that the total assets of Islamic LKNB influence economic growth in Indonesia. and f count > f table of 155.83 > 2.72. This means that sukuk, Islamic mutual funds and total assets of lknb sharia simultaneously affect economic growth in Indonesia in 2015 – 2021. The Coefficient of Determination is 0.84849, indicating that sukuk, sharia mutual funds and total assets of LKNB sharia have a very strong influence on economic growth. The proportion is 84.84%. So that, the three. control variables of corporate sukuk and total assets of lknb sharia can be economic growth factors